Intraoperative mechanical ventilation strategies for one-lung ventilation. Issue 3 (September 2015) - Şentürk, Mert; Slinger, Peter; Cohen, Edmond
Abstract : One-lung ventilation (OLV) has two major challenges: oxygenation and lung protection. The former is mainly because the ventilation of one lung is stopped while the perfusion continues; the latter is mainly because the whole ventilation is applied to only one lung. Recommendations for maintaining the oxygenation and methods of lung protection can contradict each other (such as high vs. low inspiratory oxygen fraction (FiO2 ), high vs. low tidal volume (TV), etc.). In light of the (very few) randomized clinical trials, this review focuses on a recent strategy for OLV, which includes a possible decrease in FiO2, lower TVs, positive end-expiratory pressure (PEEP) to the dependent lung, continuous positive airway pressure (CPAP) to the non-dependent lung and recruitment manoeuvres. Other applications such as anaesthetic choice and fluid management can affect the success of ventilatory strategy; new developments have changed the classical approach in this respect.